Individualized Homeopathic Management of Schizophrenia: A Long-Term Case Report (Homoeopathy for All, 2026)
Background: Schizophrenia is a chronic, severe psychiatric disorder characterized by disturbances in thought, perception, emotion, and behavior. Conventional management primarily includes antipsychotic medications and psychosocial interventions; however, long-term drug dependence, side effects, and incomplete symptom resolution often lead patients to explore complementary systems such as homeopathy. Individualized homeopathic treatment aims to address the totality of mental, emotional, and physical symptoms. Case Summary: A 42-year-old female presented with delusions of persecution, auditory hallucinations, social withdrawal, emotional suppression, and disturbed sleep since 2022. She had a history of prolonged grief, silent brooding, and marked sensitivity to emotional hurt. Based on detailed case analysis and repertorization, Natrum muriaticum was prescribed as the constitutional remedy. Results: Gradual improvement was observed over monthly follow-ups. Hallucinations reduced significantly within six months, emotional stability improved over one year, and social functioning progressively normalized. Over a two-year follow-up period (2022–2024), the patient maintained sustained improvement with no acute relapse. Conclusion: This case demonstrates the potential role of individualized homeopathic prescribing—specifically Natrum muriaticum—in the long-term management of schizophrenia. Extended follow-up suggests stable clinical improvement. Larger controlled studies are recommended.
Keywords: Schizophrenia, Homeop athy, Natrum muriaticum, Psychosis, Case report